Site and extent of amino acid digestion in dairy cattle fed with corn and its byproducts - Ferreira, Reginaldo Nassar; Bertocco Ezequiel, Jane Maria [UNESP]; Galati, Rosemary Lais; Dourado Sancanari, Juliana Borsari [UNESP]; Kronka, Sergio do Nascimento; Settimi Cysneiros, Cristine dos Santos (Univ Estadual Londrina, 2015)
The study was conducted to evaluated the site and extent of dry matter (DM), crude protein (CP), methionine (Met), lysine (Lys), and threonine (Thr) digestion of corn and byproducts obtained from corn germ mixed with different amounts of extruded or non-extruded ether extract (EE) in dairy cattle. Treatments consisted in eight types of feed and two processing in a 4 x 2 factorial design. There were four feeds: corn grain cracked (Corn), corn germ meal with 1% EE (CG1), corn germ meal with 7% EE (CG7), and corn germ meal with 10% EE (CG10). The feeds were processed in one of two ways: extruded (Ex) and not extruded. In situ techniques were used to determine DM, CP, Met, Lys, and Thr partial and total tract digestion. A basic diet was compounded of corn germ meal, soybean meal and coastcross hay in a 70: 30 roughage to concentrate ratio. There was no interaction (P>0.05) between feeds and processing method. Extrusion improved (P<0.05) total tract digestibility of corn DM but not CP. Intestinal digestibility was similar (P>0.05) for corn and corn germ meal mixed with 7 and 10% EE, regardless of EE processing method. The CP total tract digestibility of corn germ meal with 1% non-extruded EE was 16.62% higher (P<0.05) than that of the extruded form. The best total CP digestibility was obtained for corn germ meal with 7% EE, independently of the processing method. The effects of EE processing method on partial and total digestibility differed between amino acid. Corn and corn byproduct extrusion may improve dry matter digestibility, but do not necessarily influence crude protein digestion. Ruminal and intestinal digestibility of Met, Lys, and Thr depends on both feed type and processing method. Therefore, amino acid availability should be considered individually.

O estudo foi realizado para avaliar o local e a extensão da digestão da matéria seca (MS), proteína bruta (PB), metionina (Met), lisina (Lys) e treonina (Thr) em milho e seus derivados obtidos a partir do gérmen de milho, com diferentes quantidades de extrato etéreo (EE), extrusados ou não, oferecidos para gado leiteiro. Os tratamentos consistiram em oito tipos de alimentos, em arranjo fatorial 4 x 2: quatro dietas (grão de milho moído (Milho); farelo de gérmen de milho com 1% de EE (CG1); farelo de gérmen de milho com 7% de EE (CG7); farelo de gérmen de milho com 10% de EE (CG10)), e dois processamentos extrusado (Ex) e não extrusado. Utilizou-se a técnica in situ para obter a digestão total e parcial no trato da MS, PB, Met, Lys e Thr. A ração básica foi composta de farelo de gérmen de milho, farelo de soja e feno de coastcross numa relação volumoso:concentrado de 70%:30%. Não houve interação (P>0,05) entre dieta e processamento. A extrusão melhorou a digestibilidade total da MS do milho, mas não para a PB. A digestibilidade intestinal foi similar (P>0,05) entre milho e farelo de gérmen de milho com 7 e 10% de EE, independente da extrusão ou não. Sem extrusão, a digestibilidade total da PB do farelo de gérmen de milho com 1% de EE foi 16,62% maior (P<0,05), em relação a forma extrusada. A melhor digestibilidade total da PB foi obtida para farelo de germen de milho com 7% de EE, independentemente do processo. Efeitos sobre parcial ou digestibilidade total depende do aminoácido. Concluiu-se que o milho e subprodutos da extrusão poderia melhorar a digestibilidade da MS, mas não influencia necessariamente a PB. A digestibilidade ruminal e intestinal da Met, Lys e Thr depende da dieta e processamento. Portanto, a disponibilidade de aminoácidos deve ser considerada individualmente.
Local e extensão da digestão de aminoácidos em bovinos leiteiros alimentados com milho e seus subprodutos
Keywords: Extrusion; germ meal; Lysine; Methionine; Rumen; Extrusão; Farelo de gérmen; Lisina; Metionina; Rúmen